2021
DOI: 10.1186/s12916-020-01894-2
|View full text |Cite
|
Sign up to set email alerts
|

A heart failure phenotype stratified model for predicting 1-year mortality in patients admitted with acute heart failure: results from an individual participant data meta-analysis of four prospective European cohorts

Abstract: Background Prognostic models developed in general cohorts with a mixture of heart failure (HF) phenotypes, though more widely applicable, are also likely to yield larger prediction errors in settings where the HF phenotypes have substantially different baseline mortality rates or different predictor-outcome associations. This study sought to use individual participant data meta-analysis to develop an HF phenotype stratified model for predicting 1-year mortality in patients admitted with acute H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
4
8
1
Order By: Relevance
“…In‐hospital mortality was higher in HFrEF (3.4%), with no difference between HFpEF (2.2%) and HFmrEF (2.1%). This is consistent with most previous registries, although single studies have suggested similar in‐hospital or short‐term mortality in all three EF categories 15–23 . Overall, in‐hospital mortality in our mostly European cohort was low and comparable to previous large, American AHF registries (OPTIMIZE‐HF, ADHERE, GWTG‐HF) 15–17 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In‐hospital mortality was higher in HFrEF (3.4%), with no difference between HFpEF (2.2%) and HFmrEF (2.1%). This is consistent with most previous registries, although single studies have suggested similar in‐hospital or short‐term mortality in all three EF categories 15–23 . Overall, in‐hospital mortality in our mostly European cohort was low and comparable to previous large, American AHF registries (OPTIMIZE‐HF, ADHERE, GWTG‐HF) 15–17 .…”
Section: Discussionsupporting
confidence: 92%
“…The proportions of different EF categories were HFrEF 53%, HFmrEF 18%, and HFpEF 29%, consistent with previous AHF studies, with HFrEF proportions ranging from 36% to 66%, HFpEF from 17% to 43%, and HFmrEF from 13% to 25% 15–22 . In AHF diagnosed in emergency departments, HFpEF may be more common (64% in one study 23 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Heart failure (HF) with preserved ejection fraction (HFpEF) is a highly prevalent and intractable phenotype of HF which commonly occurs in patients with hypertension, metabolic diseases including type 2 diabetes mellitus (T2DM), abdominal obesity, metabolic syndrome and female gender [1,2]. Despite all-cause mortality risk and economic burden being found to be higher in HF with reduced (HFrEF) and mildly reduced (HFmrEF) ejection fraction than in HFpEF, cardiovascular (CV) death and HF-related complications, such as primary urgent hospital admission and early re-hospitalization, in patients with HFrEF/HFmrEF have exhibited a strict resemblance with those who had HFpEF [3,4].…”
Section: Introductionmentioning
confidence: 99%